2016
DOI: 10.1016/j.jacc.2016.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sacubitril/Valsartan (LCZ696) on 30-Day Readmission After Heart Failure Hospitalization

Abstract: JACC JOURNAL CMEThis article has been selected as the month's JACC Journal CME activity, available online at http://www.acc.org/jacc-journals-cme by selecting the CME tab on the top navigation bar. Accreditation and Designation StatementThe American College of Cardiology Foundation (ACCF) is accredited by the Accreditation Council for Continuing Medical Education (ACCME) to provide continuing medical education for physicians.The ACCF designates this Journal-based CME activity for a maximum of 1 AMA PRA Categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 20 publications
0
66
1
7
Order By: Relevance
“…The trial was stopped prematurely because the primary outcome, a composite of death from cardiovascular causes or hospitalization for HF, showed highly significant superiority for sacubitril/valsartan compared with enalapril: 21.8% vs. 26.5% ( P  < 0.001). The benefit was seen to a similar extent for both cardiovascular death (13.3% vs. 16.5%, P  < 0.001) and HF hospitalization (12.8% vs. 15.6%, P  < 0.001), and, remarkably, the difference between treatment groups was significant as early as Day 30 after randomization 39. Both the rate of sudden death (6.0% vs. 7.4%, P  = 0.008) and death due to worsening HF (3.5% vs. 4.4%, P  = 0.034) were reduced with sacubitril/valsartan vs. enalapril 40.…”
Section: Rationale For the Transition Studymentioning
confidence: 70%
“…The trial was stopped prematurely because the primary outcome, a composite of death from cardiovascular causes or hospitalization for HF, showed highly significant superiority for sacubitril/valsartan compared with enalapril: 21.8% vs. 26.5% ( P  < 0.001). The benefit was seen to a similar extent for both cardiovascular death (13.3% vs. 16.5%, P  < 0.001) and HF hospitalization (12.8% vs. 15.6%, P  < 0.001), and, remarkably, the difference between treatment groups was significant as early as Day 30 after randomization 39. Both the rate of sudden death (6.0% vs. 7.4%, P  = 0.008) and death due to worsening HF (3.5% vs. 4.4%, P  = 0.034) were reduced with sacubitril/valsartan vs. enalapril 40.…”
Section: Rationale For the Transition Studymentioning
confidence: 70%
“…47 Further, the benefit of sacubitril/valsartan over enalparil was not attenuated or accentuated by proximity of trial enrollment to most recent prior hospitalization for HF. 48 Unfortunately, whether these inferences can be extended to patients with currently or recently decompensated HF is not knowable from the PARADIGM trial, which excluded patients with a current episode of decompensation and patients not taking at least 4 weeks of stable medical therapy with at least 10 mg/day of enalapril or equivalent.…”
Section: Potential Expanded/future Indications Of Arni Use In Hfrefmentioning
confidence: 90%
“…The PARADIGM-HF (Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure) trial demonstrated better outcomes in HFrEF with treatment with ARNI compared to ACEI [55, 56]. Post hoc analysis of the PARADIGM-HF suggests that these benefits extend to improving clinical outcomes following hospitalization for HF and initiation should be considered during outpatient clinic visits [57]. The ongoing PIONEER-HF (comparison of sacubitril/valsartan versus enalapril on effect on NT-proBNP in patients stabilized from an acute heart failure episode) trial is a large, randomized, double-blind prospective study that aims to assess the effect on congestion by monitoring NT-proBNP levels in the post-discharge setting ().…”
Section: Augment Use Of Underused Therapies Known To Decrease Rehospimentioning
confidence: 99%